2012
DOI: 10.1016/j.yhbeh.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Robust behavioral effects of song playback in the absence of testosterone or corticosterone release

Abstract: Some species of songbirds elevate testosterone in response to territorial intrusions while others do not. The search for a general explanation for this interspecific variation in hormonal response to social challenges has been impeded by methodological differences among studies. We asked whether song playback alone is sufficient to bring about elevation in testosterone or corticosterone in the dark-eyed junco (Junco hyemalis), a species that has previously demonstrated significant testosterone elevation in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…Further, males that were more aggressive in response to an STI also elevated T to a greater degree in response to a GnRH challenge, suggesting that an STI acted on the HPG axis in the same way as GnRH (McGlothlin et al, 2007). On the other hand, in another study when male juncos were presented with 10 to 12.5 min of playback without a visual stimulus and captured approximately 30 min after the initiation of the playback, they did not show elevated T or CORT as compared to control males (Rosvall et al, 2012b). These two studies might be taken to indicate that a long social challenge elicited a hormonal response while a brief one did not.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Further, males that were more aggressive in response to an STI also elevated T to a greater degree in response to a GnRH challenge, suggesting that an STI acted on the HPG axis in the same way as GnRH (McGlothlin et al, 2007). On the other hand, in another study when male juncos were presented with 10 to 12.5 min of playback without a visual stimulus and captured approximately 30 min after the initiation of the playback, they did not show elevated T or CORT as compared to control males (Rosvall et al, 2012b). These two studies might be taken to indicate that a long social challenge elicited a hormonal response while a brief one did not.…”
Section: Introductionmentioning
confidence: 85%
“…The visual stimulus was then covered, and we waited an additional 12.5 min before attempting to capture the bird. This delay was intended to allow approximately 30 min from the initial challenge to blood sampling because T levels in circulation peak approximately 30 min after GnRH challenge (Jawor et al, 2006), and average latencies to blood sampling in prior STIs in this system were comparable (36.9, 34.9 and 27.0 min in the protocols described in McGlothlin et al (2008) and Rosvall et al (2012b)) Phase 2 (27 to 30 April) focused on longer latencies to elevate hormones (60 min song only, 60 min live lure + song). Phase 3 (4 to 19 May) employed shorter latencies (12.5 min STI with live lure) and simulated courtship interactions that included a live female lure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because all males are vying for territories and females simultaneously, competition is acute, potentially leading to the extremely elevated levels of T found in high-latitude birds during early breeding (Hunt et al 1995;Romero et al 1998;Meddle et al 2002). Additionally, work in dark-eyed juncos (Junco hyemalis) has shown that males with particularly high T levels have mates that are fertile (McGlothlin et al 2008;Rosvall et al 2012); the extremely high levels of androgens if the rufous-collared sparrow could partially be due to the presence of fertile females. During early breeding, most of the females we caught had brood patches of two or three.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the focus has shifted to testing whether low-amplitude singing can serve as an honest signal of behavioral intent , Ballentine et al 2008, Hof and Hazlett 2010, Templeton et al 2012, and whether low-amplitude songs are salient signals that elicit responses from both male (Balsby and Dabelsteen 2005, Lampe et al 2010, Reichard et al 2011, Anderson et al 2012, Rosvall et al 2012) and female receivers (Anderson et al 2007). The dominant focus of this research has emphasized the aggressive function of low-amplitude singing, and its surprising ability to predict a physical attack more reliably than other signaling strategies such as song-type matching or song overlapping (Searcy and Beecher 2009, Ręk and Osiejuk 2011, Akçay et al 2013.…”
Section: Introductionmentioning
confidence: 99%